Cyton2: A Model of Immune Cell Population Dynamics That Includes Familial Instructional Inheritance - Cheon, HoChan; Kan, Andrey; Prevedello, Giulio; Oostindie, Simone C.; Dovedi, Simon J.; Hawkins, Edwin D.; Marchingo, Julia M.; Heinzel, Susanne; Duffy, Ken R.; Hodgkin, Philip D. (Frontiers in Bioinformatics, 2021)
Lymphocytes are the central actors in adaptive immune responses. When challenged with antigen, a small number of B and T cells have a cognate receptor capable of recognising and responding to the insult. These cells proliferate, building an exponentially growing, differentiating clone army to fight off the threat, before ceasing to divide and dying over a period of weeks, leaving in their wake memory cells that are primed to rapidly respond to any repeated infection. Due to the non-linearity of lymphocyte population dynamics, mathematical models are needed to interrogate data from experimental studies. Due to lack of evidence to the contrary and appealing to arguments based on Occam’s Razor, in these models newly born progeny are typically assumed to behave independently of their predecessors. Recent experimental studies, however, challenge that assumption, making clear that there is substantial inheritance of timed fate changes from each cell by its offspring, calling for a revision to the existing mathematical modelling paradigms used for information extraction. By assessing long-term live-cell imaging of stimulated murine B and T cells in vitro, we distilled the key phenomena of these within-family inheritances and used them to develop a new mathematical model, Cyton, that encapsulates them. We establish the model’s consistency with these newly observed fine-grained features. Two natural concerns for any model that includes familial correlations would be that it is overparameterised or computationally inefficient in data fitting, but neither is the case for Cyton. We demonstrate Cyton ’s utility by challenging it with high-throughput flow cytometry data, which confirms the robustness of its parameter estimation as well as its ability to extract biological meaning from complex mixed stimulation experiments. Cyton, therefore, offers an alternate mathematical model, one that is more aligned to experimental observation, for drawing inferences on lymphocyte population dynamics.